Сучасні реалії соціального захисту осіб з інвалідністю в Україні - Букартик, Анастасія Михайлівна; Bukartyk, Anastasiia Mykhailivna (Національний університет "Львівська політехніка", 2024)
The issue of social protection for persons with disabilities in Ukraine is relevant in the context of implementing European standards of social inclusion. Analysis of scientific research indicates the presence of systemic challenges in this area, related to insufficient funding, imperfection of the regulatory and legal framework, and organizational mechanisms for providing social services to persons with disabilities (Petrenko & Kovalchuk, 2024). Special attention is needed for the transformation of approaches to ensuring social guarantees for persons with disabilities, taking into account international standards, particularly the provisions of the UN Convention on the Rights of Persons with Disabilities. Research object: the system of social protection for persons with disabilities in Ukraine. Research subject: the current state, peculiarities of functioning, and prospective directions for the development of the social protection system for persons with disabilities in Ukraine. Research objective: comprehensive analysis of the current state of the social protection system for persons with disabilities in Ukraine and its transformation as a result of reforms in recent years. Research results: The work examines problems of the current social protection system for persons with disabilities: insufficient funding of programs, regional imbalances in access to social services, slow pace of deinstitutionalization. Recommendations have been developed aimed at improving mechanisms of social protection for persons with disabilities in the context of Ukraine's European integration, decentralization, and digital transformation of the social services system. Keywords: social protection, persons with disabilities, inclusion, state support, social services. REFERENCES Law of Ukraine "On the Fundamentals of Social Protection of Persons with Disabilities in Ukraine" dated March 21, 1991 No. 875-XII (as amended on January 1, 2023). URL: https://zakon.rada.gov.ua/laws/show/875-12 Zhukova, N. V. (2022). Improvement of the social benefits system for persons with disabilities in the context of European integration. Economy and State, 11, 89-96. URL: http://www.economy.in.ua/pdf/11_2022/15.pdf

Проблематика соціального захисту осіб з інвалідністю в Україні є актуальним в контексті впровадження європейських стандартів соціальної інклюзії. Аналіз наукових досліджень свідчить про наявність системних викликів у цій сфері, пов'язаних із недостатнім фінансуванням, недосконалістю нормативно-правової бази та організаційних механізмів надання соціальних послуг особам з інвалідністю (Петренко & Ковальчук, 2024). Особливої уваги потребує трансформація підходів до забезпечення соціальних гарантій для осіб з інвалідністю з урахуванням міжнародних стандартів, зокрема положень Конвенції ООН про права осіб з інвалідністю. Об'єкт дослідження: система соціального захисту осіб з інвалідністю в Україні. Предмет дослідження: сучасний стан, особливості функціонування та перспективні напрямки розвитку системи соціального захисту осіб з інвалідністю в Україні. Мета дослідження: комплексний аналіз сучасного стану системи соціального захисту осіб з інвалідністю в Україні, та її трансформації внаслідок реформ останніх років. Результати дослідження: в роботі досліджено проблеми чинної системи соціального захисту осіб з інвалідністю: недостатнє фінансування програм, регіональні дисбаланси у доступі до соціальних послуг, повільні темпи деінституціалізації. Розроблено рекомендації, спрямовані на вдосконалення механізмів соціального захисту осіб з інвалідністю в контексті європейської інтеграції України, децентралізації та цифрової трансформації системи соціальних послуг. Ключові слова: соціальний захист, особи з інвалідністю, інклюзія, державна підтримка, соціальні послуги. Список використаних джерел Закон України «Про основи соціальної захищеності осіб з інвалідністю в Україні» від 21.03.1991 No 875-XII (в редакції від 01.01.2023). URL: https://zakon.rada.gov.ua/laws/show/875-12 Жукова, Н. В. (2022). Удосконалення системи соціальних виплат особам з інвалідністю в контексті європейської інтеграції. Економіка та держава, 11, 89-96. URL: http://www.economy.in.ua/pdf/11_2022/15.pdf
Current realities of social protection of persons with disabilities in Ukraine
Keywords: 6.232.00.00